2013
DOI: 10.1128/jcm.01930-13
|View full text |Cite
|
Sign up to set email alerts
|

Precise Dissection of an Escherichia coli O157:H7 Outbreak by Single Nucleotide Polymorphism Analysis

Abstract: The current pathogen-typing methods have suboptimal sensitivities and specificities. DNA sequencing offers an opportunity to type pathogens with greater degrees of discrimination using single nucleotide polymorphisms (SNPs) than with pulsed-field gel electrophoresis (PFGE) and other methodologies. In a recent cluster of Escherichia coli O157:H7 infections attributed to salad bar exposures and romaine lettuce, a subset of cases denied exposure to either source, although PFGE and multiple-locus variable-number t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…S3). For presentation, we limited our displayed data to only a few key strains in the E. coli O157:H7 literature, several notable intermediates, and an outbreak from lettuce in salad bars in a multistate outbreak (37). This representation is not meant to suggest we have found the strains implicated in any outbreak directly, but simply to ascertain whether the genetic content of our strains is or is not similar to isolates that have caused outbreaks, thus providing evidence for their pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…S3). For presentation, we limited our displayed data to only a few key strains in the E. coli O157:H7 literature, several notable intermediates, and an outbreak from lettuce in salad bars in a multistate outbreak (37). This representation is not meant to suggest we have found the strains implicated in any outbreak directly, but simply to ascertain whether the genetic content of our strains is or is not similar to isolates that have caused outbreaks, thus providing evidence for their pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Turabelidze and colleagues [16] sequenced pathogenic E. coli that was congregated by PFGE. It was reported that these isolates had identical PFGE band, but their differences were revealed by sequencing.…”
Section: Convergence Of E Coli Isolatesmentioning
confidence: 99%
“…Nowadays, sequence-based typing approaches using whole-genome sequence (WGS) data are overcoming these obstacles. Several studies on various bacterial species have already shown that WGS-based typing, based either on single nucleotide variants (SNVs) (9,10) or on gene-by-gene allelic profiling of core genome genes, frequently named core genome MLST (cgMLST) (11)(12)(13), currently represents the ultimate tool for strain subtyping. Moreover, it was recently shown in an international ring trial that cgMLST is highly reproducible (14).…”
mentioning
confidence: 99%